Contribution of veterinary sector to antimicrobial resistance in One Health compendium: an insight from available Indian evidence - Chakraborty, Debjit; Debnath, Falguni; Giri, Sandip; Saha, Shatabdi; Pyne, Soume; Chakraverty, Raja; Majumdar, Agniva; Deb, Alok Kumar; Bhatia, Rajesh; Dutta, Shanta (Frontiers in Veterinary Science, 2024)
Application of antibiotics in the poultry and veterinary sectors are very common practice in India. Owing to the seriousness of the antimicrobial resistance the present study has illustrated the overall scenario of antimicrobial resistance (AMR) in the poultry and veterinary sectors in India through an in-depth scoping review and key informants' interview (KII). In poultry sector, most of the studies reviewed have reported the resistant bacteria isolated from chicken meat, eggs, cloacal swab, fecal samples and only few have reported the presence of resistant bacteria in and around the environment of poultry farms. The major resistant bacteria that have been reported are E. coli, Salmonella spp., S. aureus, Campylobacter jejuni, K. pneumoniae. These bacterial isolates exhibited resistance to various antibiotics, such as azithromycin (21.43%), tetracycline (11.30 -100%), chloramphenicol (4.76 -100%), erythromycin (75 -83.33%), ciprofloxacin (5.7 -100%), gentamicin (17 -100%), amikacin (4.76%), cotrimoxazole (42.2 -60%), trimethoprim (89.4%), ceftriaxone (80%), and cefotaxime (14.29 -70%). Like the poultry sector, different antibiotics are also used for treating clinical and subclinical bovine mastitis which is one of the major problems plaguing the dairy sector. Several AMR bacterial strains like E. coli, Staphylococcus aureus, S. epidermidis, and Klebsiella pneumoniae have been reported by many researchers which showed resistance against tetracycline (74%), oxytetracycline (47.37%), ciprofloxacin (51%), streptomycin (57.89%), cephalosporin (100%), trimethoprim (70%). The key informants' interviews have revealed several reasons behind these AMR scenarios of which growing need for the production of food animals and their products with inadequate infrastructure and lack of proper knowledge on farm management among the farmers are the major ones. Though the several government legislations and policies have been laid down however, proper implementation of these policies, strict surveillance on antibiotic application in poultry and veterinary sectors, awareness generation among the farmers and infrastructure development can help to minimize the development and transmission of AMR bacteria within and from these sectors.